The Condition of Education Science in the Republic: Information Dimension - Dagytė, Ina (Acta Paedagogica Vilnensia, 1991)
The article discusses the development of science of pedagogy during 1973-1987, on the basis of the classification of pedagogical disciplines offered by Leonas Jovaiša, which distinguishes theoretical pedagogy (general pedagogy, didactics, theory of education, methodology of pedagogy, andragogy, historical and comparative pedagogy) and applied pedagogy (methods of teaching, educational methods, social pedagogy, psychological pedagogy, institutional pedagogy, special education). The main focus is the dynamics of pedagogical scientists and scientific publications, as well as the correlation between these two factors. During the period under discussion 192 dissertations in pedagogy have been defended. The majority of scholars defended the theses of the theory and history of pedagogy, in second place – teaching methods, in the third – special education. However, the growth of scientific publications is not so pronounced. It is observed that the productivity of researchers is greatly reduced after the defence of the dissertation.